Remittances, finance and industrialisation in Africa - Uchenna Rapuluchukwu Efobi; Simplice Asongu; Chinelo Okafor; Vanessa Tchamyou; Belmondo Tanankem Voufo (African Governance and Development Institute (AGDI), 2019)
The paper assesses how remittances directly and indirectly affect industrialisation us ing a panel of 49 African countries for the period 1980-2014. The indirect impact is assessed through financial development channels. The empirical evidence is based on three interactive and non-interactive simultaneity-robust estimation techniques, namely: (i) Instrumental Fixed Effects (FE) to control for the unobserved heterogeneity; (ii) Generalised Method of Moments (GMM) to control for persistence in industrialisation and (iii) Instrumental Quantile Regressions (QR) to account for initial levels of industrialisation. The non-interactive specification elucidates direct effects of remittances on industrialisation whereas interactive specifications explain indirect impacts. The findings broadly show that for certain initial levels of industrialisation, remittances can drive industrialisation through the financial development mechanism. Policy implications are discussed.
Keywords: F24; F43; G20; O55; 330; Africa; Diaspora; Financial development; Industrialisation; Remittances